A Systematic Review of Technologies to Teach Control Structures in Preschool Education - Bakala, Ewelina; Gerosa, Anaclara; Hourcade, Juan Pablo; Tejera, Gonzalo; Peterman, Kerry; Trinidad, Guillermo (Frontiers in Psychology, 2022)
There is growing interest in teaching computational thinking (CT) to preschool children given evidence that they are able to understand and use CT concepts. One of the concepts that is central in CT definitions, is the concept of control structures, but it is not clear which tools and activities are successful in teaching it to young learners. This work aims at 1) providing a comprehensive overview of tools that enable preschool children to build programs that include control structures, and 2) analyzing empirical evidence of the usage of these tools to teach control structures to children between 3 and 6. It consists of three parts: systematic literature review (SLR) to identify tools to teach CT to young children, analysis of tools’ characteristics and the possibilities that they offer to express control structures, and SLR to identify empirical evidence of successful teaching of control structures to young children using relevant tools. This work provides an understanding of the current state of the art and identifies areas that require future exploration.